(untitled) (Asian Journal of Medical Sciences, 2024)
Background: The prevalence of imposter phenomenon (IP) is more among students, engineers, health-care-professionals, and researchers. Medical students are particularly predisposed to IP due to stressors like a highly competitive environment both preceding and during medical education. Aims and Objectives: The aims and objectives of the study are to find out the prevalence of IP among undergraduate medical students of a Medical College of Eastern India and to elicit the relationship between background factors and IP. Materials and Methods: One hundred and thirty medical students were selected by stratified random sampling from all four semesters. Twenty point Clance IP scale was used to measure IP. It contains 20 questions, each of them having five options. A score between “60 and 80” indicates frequent imposter syndrome and a score higher than 80 indicates intense imposter feeling. After conducting descriptive analysis, ordinal logistic regression was conducted. Results: Among the study subjects 37.7% had frequent imposter feelings and 10.8% had intense imposter feelings. High level of IP (frequent and intense combined) is more common among second-semester students, females, middle class, those who sleep >56 h/week, who perceived their school performance was good, who have a family history of psychiatric illness, and who take some kind of chronic medication. As per Ordinal regression, second-semester, middle class, good school performance, and history of chronic medication were found to be significant predictors of higher degree IP. Conclusion: The prevalence of IP is alarming among medical students and it is high time to address this before it turns into graver psychiatric morbidity.